INFLUENCE OF COLD TEMPERATURE ANNEALING ON OPTICAL PROPERTIES OF SYSTEM «POLYIMIDE – YBa2Cu3O6+x» - Muradov, A. D. (Recent Contributions to Physics, 2009)
To consider influence of cold temperature annealing on IR-spectrums of absorption of system «POLYIMIDE – YBa2Cu3O6+x». Investigation spectrums before and after annealing, and also the analysis of their change is made.